Validation of Diagnostic Codes to Identify Carbon Monoxide Poisoning in Taiwan’s Claims Data - Chiang, Min-Ying; Shao, Shih-Chieh; Liao, Shu-Chen (Frontiers in Pharmacology, 2022)
Previous studies identified the study cohort or outcome of carbon monoxide poisoning (COP) by using the relevant disease diagnosis codes in secondary databases, but the validity of diagnosis codes of COP is unclear in such secondary databases. This study aimed to evaluate the accuracy of case definitions for COP using the ICD-9-CM and ICD-10-CM diagnosis codes in Taiwan’s health insurance claims data. Methods: We selected a 10% simple random sample from an original cohort of patients newly undergoing carboxyhemoglobin (COHb) testing under any clinical diagnosis at four Chang Gung Memorial Hospitals in Taiwan during 2011-2020. Two clinical doctors independently ascertained the COP diagnosis by reviewing the medical records as the reference standard. We estimated the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of various case definitions (e.g., ICD-9-CM code, ICD-10-CM code and the uses of hyperbaric oxygen therapy) in the claim data. Results: We randomly selected the 557 cases from the original cohort of a total of 5,571 cases newly receiving COHb test in the study hospitals. We found 90, 35, and 9 cases were true-positive, false-positive, and false-negative episodes of COP, respectively, among 278 cases with an ICD-9-CM code of 986. A further 111, 34, and 6 cases were true-positive, false-positive, and false-negative episodes of COP, respectively, among 279 cases with ICD-10-CM codes of T58. Using ICD-9-CM codes, the sensitivity, specificity, PPV and NPV for COP were 90.9%, 80.4%, 72% and 94.1%, respectively. Using ICD-10-CM codes they were 94.9%, 79%, 76.6% and 95.5%, respectively. PPV typically increased when COP was the primary diagnosis and could reach 100% if patients with ICD-CM code 986 or T58 also received hyperbaric oxygen therapy during hospitalization.